Six Cases of Esophagogastric Junctional Cancer Successfully Treated with Neoadjuvant Chemotherapy - Hiroi, So; Fukuda, Shintaro; Yamahata, Yuto; Otani, Takahiro; Tada, Tetsuya; Hirukawa, Hiroshi (Gan to kagaku ryoho, 2023)
Neoadjuvant chemotherapy(NAC)is prescribed for resectable esophagogastric junctional cancer on the basis of esophageal invasion length, lymph node metastasis, and pathological diagnosis. Due to a lack of consensus in Japan, however, discussion regarding its use is necessary. This study comprised 6 patients who underwent surgical resection after receiving NAC in our department from 2018 to 2022. All the patients were male, with a median age of 67 years. Three patients underwent SP therapy, 2 received SOX therapy, and 1 received both SOX and HER therapy. A total gastrectomy was performed in 3 cases, a fundectomy in 1 case, and a subtotal esophagectomy with gastric tube reconstruction in 2 cases. The histological types were tub2 in 3 cases; and tub1 plus pap, por1 plus pap, and NEC in 1 case each, respectively. One case was ypStage ⅠA, 2 cases were ⅠB, 1 was ⅡA, 1 was ⅡB and 1 was pCR. Currently, all the patients remain alive and without recurrence. NAC has, therefore, been demonstrated to be an effective therapeutic strategy for esophagogastric junctional cancer in this study. However, further research with a larger sample size is required.